Social Capital Contributions to Resilience in an Entrepreneurial Ecosystem in Nepal (Journal of Tourism and Himalayan Adventures, 2023)
Tourism is an important sector for many people in Nepal. There have been a number of damaging shocks in the last decade, including the 2015 earthquake and the COVID-19 pandemic, that have stopped the industry in its tracks. The effects of slow onset climate change are also impacting the industry and are forecast to get worse. An entrepreneurial ecosystem in Nepal has been established to foster resilience among participating businesses. This research addresses whether social capital contributes to the resilience of tourism startups in Nepal and whether an entrepreneurial ecosystem fosters that social capital. Further, it asks whether renewable energy and energy efficient practices have impacted resilience. And, finally, whether there is evidence of transformative change within the businesses studied. Results suggest that relationships generated through enduring historical shocks in the tourism economy in Nepal have fostered social capital, and that the entreprenuerial ecosystem has itself cultivated elements of social capital and resilience in the participating businesses. While firm conclusions could not be drawn as to whether transformative change has occurred in the businesses, the foundation for realising transformational opportunities has been established. This study suggests that resilience can be reframed from its historically ecological confines to be a more fluid and adaptable concept of human agency affected socio-ecological systems and may eventually allow, and be a driver of, transformational change in businesses participating in an entrepreneurial ecosystem.